The halo+cluster system of the Galactic globular cluster NGC 1851 - Marino, A. F.; Milone, A. P.; Yong, D.; Dotter, A.; Da Costa, G.; Asplund, M.; Jerjen, H.; Mackey, D.; Norris, J.; Cassisi, S.; Sbordone, Luca; Stetson, P. B.; et al. (Monthly notices of the Royal Astronomical Society, 2014)
Abstract. NGC 1851 is surrounded by a stellar component that extends more than 10 times beyond the tidal radius. Although the nature of this stellar structure
Gesehen am 29.07.2020